Psoriatic Arthritis and Psoriasis Pathology and Clinical Aspects - Adebajo, Adewale; Boehncke, Wolf-Henning; Gladman, Dafna D.; Mease, Philip J. (Springer International Publishing : Imprint: Springer, 2016)
This useful book addresses the advances in the development of new approaches to assess and treat psoriasis and psoriatic arthritis. The authors' commitment in advancing knowledge in the fields of these diseases has been greatly helped by organisations such as the group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA), which have been at the forefront of education and research into these conditions, alongside other interested international and national organisations. Psoriatic Arthritis and Psoriasis -Pathology and Clinical Aspects is a comprehensive and authoritative book written by experts in the field, aimed at generalists and specialists, researchers and clinicians, together with other health care professionals who look after patients with these conditions.